(untitled) (Acta Entomologica Serbica, 2021)
Sixty-one adult individuals of 15 species (10 genera) and one subspecies of Pselaphinae were caught using a car-net during a single evening trip in the valley of the Lumnica River, village of Alipostivan, close to the town of Përmet, southern Albania, on 22.05.2018. The following five species are new for the beetle fauna of Albania: Trimium expandum Reitter, 1884, Meliceria (Cyrtoplectus) stankoi (Karaman, 1960), Brachygluta (Brachygluta) epirotica Sabella, 2004, Bythinus tener Reitter, 1884 and Tychobythinus latifrons (Müller, 1902). The prevailing weather (air) conditions between 7:00 and 8:30 pm on the day of collecting (at Gjirokastër, 30 km away), with a warm although decreasing temperature (27.2-25.6°C) and increasing humidity (46-53%), were obviously optimal for the car-net method.